Barriers and Enablers to Implementing a High-Dependency Care Model in Pediatric Care: A Preimplementation Study. Issue 4 (October 2019) - Cassidy, Christine; MacEachern, Lauren; Egar, Jeanne; Best, Shauna; Foley, Laura; Rowe, Mary Elizabeth; Curran, Janet
Abstract : Background: As the level of acuity of pediatric hospital admissions continues to increase, additional pressure is being placed on hospital resources and the nursing workforce. Local Problem: Currently, there is no formalized approach to care for high-acuity patients on our pediatric inpatient unit. Methods: We used a qualitative descriptive design, guided by the Theoretical Domains Framework and Capability, Opportunity, Motivation-Behaviour (COM-B) model, to conduct focus groups and interviews with clinicians and administrators to identify potential barriers and enablers to implementing a high-dependency care (HDC) model. An HDC model focuses on the relationship between adequate nursing staff resources and patient acuity to improve patient health outcomes. Results: Participants identified the need for clear guidelines and supportive physical structures to facilitate HDC implementation. Anticipated benefits included enhanced nursing confidence and family-centered care. Conclusions: Study findings highlight multilevel factors to consider prior to implementing an HDC model on a pediatric inpatient unit. Abstract : Supplemental Digital Content is Available in the Text.